Prenatal arsenic exposure induces immunometabolic alteration and renal injury in rats - Singh, Radha Dutt; Tiwari, Ratnakar; Sharma, Vineeta; Khan, Hafizurrahman; Gangopadhyay, Siddhartha; Singh, Sukhveer; Koshta, Kavita; Shukla, Shagun; Arjaria, Nidhi; Mandrah, Kapil; Jagdale, Pankaj Ramji; Patnaik, Satyakam; et al. (Frontiers in Medicine, 2023)
Arsenic (As) exposure is progressively associated with chronic kidney disease (CKD), a leading public health concern present worldwide. The adverse effect of As exposure on the kidneys of people living in As endemic areas have not been extensively studied. Furthermore, the impact of only prenatal exposure to As on the progression of CKD also has not been fully characterized. In the present study, we examined the effect of prenatal exposure to low doses of As 0.04 and 0.4 mg/kg body weight (0.04 and 0.4 ppm, respectively) on the progression of CKD in male offspring using a Wistar rat model. Interestingly, only prenatal As exposure was sufficient to elevate the expression of profibrotic (TGF-β1) and proinflammatory (IL-1α, MIP-2α, RANTES, and TNF-α) cytokines at 2-day, 12- and 38-week time points in the exposed progeny. Further, alteration in adipogenic factors (ghrelin, leptin, and glucagon) was also observed in 12- and 38-week old male offspring prenatally exposed to As. An altered level of these factors coincides with impaired glucose metabolism and homeostasis accompanied by progressive kidney damage. We observed a significant increase in the deposition of extracellular matrix components and glomerular and tubular damage in the kidneys of 38-week-old male offspring prenatally exposed to As. Furthermore, the overexpression of TGF-β1 in kidneys corresponds with hypermethylation of the TGF-β1 gene-body, indicating a possible involvement of prenatal As exposure-driven epigenetic modulations of TGF-β1 expression. Our study provides evidence that prenatal As exposure to males can adversely affect the immunometabolism of offspring which can promote kidney damage later in life.